2016
DOI: 10.1016/j.ebiom.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Brain Correlates of Human Leukocyte Antigen (HLA) Protection in Gulf War Illness (GWI)

Abstract: BackgroundWe recently reported that six alleles from class II genes of the Human Leukocyte Antigen (HLA) confer protection from Gulf War Illness (GWI) (Georgopoulos et al., 2015). The most significant effect is exerted on Neurological-Cognitive-Mood (NCM), Pain, and Fatigue symptoms, such that higher number of copies of the protective alleles are associated with lower symptom severity. Here we tested the hypothesis that this effect is exerted by modulating the strength of neural synchronicity.MethodsEighty-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…As such, both human and animal studies have suggested a connection between physiological stress and the immune system, both systemically and in the brain. The findings presented by James et al (2016) support the notion that GWI is a disease in which genetically-regulated sensitivity of the immune system interacts with exposures that occurred in the Gulf War to reprogram neural functioning. The importance of such studies is highlighted by the emphasis of the Gulf War Illness Research Program of the Department of Defense's Congressionally Directed Medical Research Programs (CDMRP), where the need for research to address the role of neurological and immune dysfunction, as well as genetic predisposition in GWI is a current priority.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…As such, both human and animal studies have suggested a connection between physiological stress and the immune system, both systemically and in the brain. The findings presented by James et al (2016) support the notion that GWI is a disease in which genetically-regulated sensitivity of the immune system interacts with exposures that occurred in the Gulf War to reprogram neural functioning. The importance of such studies is highlighted by the emphasis of the Gulf War Illness Research Program of the Department of Defense's Congressionally Directed Medical Research Programs (CDMRP), where the need for research to address the role of neurological and immune dysfunction, as well as genetic predisposition in GWI is a current priority.…”
supporting
confidence: 63%
“…The importance of such studies is highlighted by the emphasis of the Gulf War Illness Research Program of the Department of Defense's Congressionally Directed Medical Research Programs (CDMRP), where the need for research to address the role of neurological and immune dysfunction, as well as genetic predisposition in GWI is a current priority. Not only does the work of James et al (2016) address all of these areas of interest, but it also supports the expansion of this work into other relevant genetic/immune based studies. Such studies are underway in animal models where genetically defined strains of mice, which combine a toxicologically susceptible mouse strain with a more resistant strain (Jones et al, 2013) can be used to replicate a genetically diverse population to evaluate genetic-based neuroimmune susceptibility to GWI.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…For example, compared to healthy control veterans, veterans with GWI showed an average of 10.4% reduction in cerebellar volume and 2 × the rate of reduction of cerebellar gray matter volume with age (− 14%/decade in GWI vs. − 6.9%/decade in controls). We concluded that the marked subcortical volume reduction observed in veterans with GWI is likely attributable to direct exposure to toxins, akin to toxic encephalopathy ( Valk and van der Knaap, 1992 ), in combination with lack of immunogenetic protection in GWI ( Georgopoulos et al, 2016 , James et al, 2016 ).…”
Section: Introductionmentioning
confidence: 97%
“…HLA genes are located in the Major Histocompatibility Complex (MHC) of chromosome 6 and play a central role in immune system functioning ( Meuer et al, 1982 ). We previously demonstrated that six HLA class II alleles (DRB1*01:01, DRB1*08:11, DRB1*13:02, DQB1*02:02, DPB*01:01, DPB1*06:01) successfully discriminate veterans with GWI from controls ( Georgopoulos et al 2016 ) and interact with brain function to influence symptoms of GWI ( James et al, 2016 ). We also found an inverse relation between GWI symptom severity and the number of copies of the 6 protective HLA alleles, and that the frequency of those 6 alleles in veterans with GWI is significantly lower than in unaffected veterans ( Georgopoulos et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%